Respon Petani Padi Terhadap Program Kartu Tani (Kasus di Kelompok Tani Karya Bhakti I di Desa Gegesik Kidul, Kecamatan Gegesik, Kabupaten Cirebon) - Ghifari, Reza Affan; Kusumo, Rani Andriani Budi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
In order to facilitate fertilizer subsidies for farmers, the government created a card-based fertilizer subsidy program called Kartu Tani. The Kartu Tani program aims to ensure that farmers receive fertilizer quotas that suit their needs and have access to purchase subsidized fertilizer, however, in the implementation process there are various problems such as the lack of absorption of subsidized fertilizer through the Kartu Tani, a reduction in subsidized fertilizer variants, and the use of the Kartu Tani. not as recommended. At the research location, there is a problem, namely the low level of absorption of subsidized fertilizer through Kartu Tani in 2023. This research aims to analyze farmers' responses to Kartu Tani program in Gegesik Kidul Village, Cirebon Regency. In this research, a quantitative research design was used using a questionnaire as a primary data collection method which was then analyzed using descriptive analysis. This research uses the census method. The respondents in this study were all members of the Karya Bhakti I Farmer Group who had active Kartu Tani Cards totaling 55 people. The research results showed that the implementation of the Farmer's Card program at the farmer research location did not comply with procedures regarding the use of the Kartu Tani by farmers. Apart from that, farmers' response to Kartu Tani program was not good. This is motivated by farmers' low understanding of the Kartu Tani Card and a lack of assistance. Using Kartu Tani that do not comply with procedures can increase the potential for misuse of subsidized fertilizers. Therefore, maximum assistance is needed from various parties.